2011
DOI: 10.1007/s10802-011-9580-9
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Effects of Incredible Years as a Preventive Intervention in Preschool Children with Conduct Problems

Abstract: The present study evaluated preventive effects of the Incredible Years program for parents of preschool children who were at risk for a chronic pattern of conduct problems, in the Netherlands. In a matched control design, 72 parents of children with conduct problems received the Incredible Years program. These families (intervention group) were compared with 72 families who received care as usual (control group). Two years after termination of the intervention, it appeared that observed and selfrated parenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 45 publications
3
56
1
8
Order By: Relevance
“…Earlier work, however, often showed inconsistencies and some elements of harsh and inconsistent parenting practices, especially corporal punishment, have not always been shown to be affected by the intervention (e.g. Posthumus et al 160 ). Some of these inconsistencies may have been because of the instruments used.…”
Section: Results and Discussion Of Wider Health Benefits And Possiblementioning
confidence: 99%
“…Earlier work, however, often showed inconsistencies and some elements of harsh and inconsistent parenting practices, especially corporal punishment, have not always been shown to be affected by the intervention (e.g. Posthumus et al 160 ). Some of these inconsistencies may have been because of the instruments used.…”
Section: Results and Discussion Of Wider Health Benefits And Possiblementioning
confidence: 99%
“…Two studies described families as middle to high status (Jalali, Shaeeri, Tahmasian, & Pourahmadi, 2009;Leung et al, 2003). Five trials provided no information about income or SES Larsson et al, 2009;Matos, Bauermeister, & Bernal, 2009;Posthumus, Raaijmakers, Maassen, van Engeland, & Matthys, 2012). In all but three studies Scott et al, 2001), the great majority of families were ethnically native to the country in which the trial took place.…”
Section: Included Studiesmentioning
confidence: 99%
“…Eleven trials used a waitlist control; two used no-intervention control groups (Jalali et al, 2009;Leung et al, 2009); and three, TAU (Ogden & Hagen, 2008;Posthumus et al, 2012;Sigmarsdó ttir et al, 2013). The three studies with a TAU condition provided descriptions of the services offered to control participants but few details on dosage or nature of treatment.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Smit et al, 2008;Kaminski, Valle, Filene & Boyle, 2008) indicated that these interventions have demonstrated efficacy in preventing substance use and other child problem behaviors. These positive results have been reported in different settings (Aalborg et al, 2010;Letarte, Normandeau & Allard, 2010;Redmond et al, 2009;Henggeler & Schoenwald, 2011;Brook, McDonald & Yan, 2012;Donavan, Wood, Frayjo, Black & Surette, 2012), target groups (Mindel & Hoefer, 2006;Orte, Touza, Ballester & March, 2008;McDaniel, Braiden, Onyekwelu, Murphy & Regan, 2011;Posthumus, Raaimakers, Maassen, Engeland, & Matthys, 2012;Kumpfer, Whiteside, Greene & Allen, 2010), cultures (Skärstrand, Larsson & Andréasson, 2008;Pérez, et al, 2009;Kumpfer, Xie & O'Driscoll, 2012;Brotman et al, 2009;Ortega, Giannotta, Latina & Ciairano, 2012) and addicted behaviours (Trudeau, Spoth, Randall & Azevedo, 2007;Zhong, et al, 2011;Donovan et al, 2012). …”
Section: Objeto Y Alcance De La Presente Revisión Bibliográficamentioning
confidence: 73%